(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE; To determine the health-related quality of life and functional outcome after dual mobility total hip replacement at Tertiary Care Hospital in Karachi. STUDY DESIGN; This study followed a descriptive cross-sectional framework. PLACE AND DURATION OF THE STUDY; This research was executed at the Department of Orthopedics Civil Hospital, Karachi from 1st August 2024 to 1st February 2025 METHODOLOGY; The sample of 60 patients aged 35–60 years of both gender undergoing dual mobility total hip arthroplasty for femoral neck fractures were included int the study through non-probability consecutive sampling, eligible patients were assessed for functional outcomes via the Harris Hip Score and HRQOL via SF-36. Data was analyzed using SPSS v26.0 (p < 0.05). RESULTS: In 60 patients (mean age 62.02 ± 8.82 years, BMI 25.95 ± 3.51 kg/m²), the mean Harris Hip Score was 90.52 ± 8.77 (95% CI: 88.25–92.78), with 61.7% excellent, 25.0% good, 11.7% fair, and 1.7% poor outcomes. SF-36 domain scores ranged from 67.52 ± 15.27 (vitality) to 71.99 ± 15.43 (mental health). No statistically significant associations were found between age (p=0.446), gender (p = 0.654), and functional outcomes. CONCLUSION: Dual mobility total hip arthroplasty demonstrated excellent short-term functional outcomes and significant improvements in health-related quality of life among patients with femoral neck fractures. With a high proportion of excellent and good results and low complication rates, this approach appears to be a reliable surgical option in similar clinical settings, offering enhanced stability and patient satisfaction.